Gender-Based Violence within the Rohingya Community in Bangladesh: Intersectional Experiences of Victimization (Social Science Review, 2026)
Experiences of Rohingya women in exile have long seen the need to be understood in the layered identities they carry. This article attempts to apply an intersectional lens to analyze the complex nature of gender-based violence (GBV) experienced by Rohingya women in Cox’s Bazar, Bangladesh. The study argues that a single-axis analysis is insufficient to understand the full length of victimization, as it fails to account for the compounded vulnerabilities that come about from intersecting identities such as gender, statelessness, displacement, religion, and poverty. Through the adoption of qualitative research using in-depth interviews and focus group discussions with 25 Rohingya women and 27 key informants, the study brings forth persistent patterns of GBV, including intimate partner violence, forced child marriage, dowry abuse, and abduction. The findings reveal that persistent patriarchal norms, a culture of shame, and inadequate legal protections normalize these crimes. The absence of formal justice within the Rohingya camps further enhances the vulnerability of statelessness, forcing Rohingya women to depend on informal, male-dominated power structures. The study argues for a shift from how victimization of this community is perceived and the application of intersectional approaches to understand the true nature of violence suffered and empower Rohingya women as agents of change.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025; pp. 1-22.